Dielectric characteristics of a Ce3+-doped Sr0.61Ba0.39Nb2O6 single crystal with Cole-Cole plots technique - Sentürk , E (Academic Press Inc Elsevier Science, 2004)
In this paper, we have investigated relaxation mechanisms and dielectric characteristics of an Sr0.61-xBa0.39Nb2O6Cex (abbreviated as SBN61 and x=0.0066) single crystal with dielectric spectroscopy measurements. The crystal undergoes a ferroelectric phase transition at 340K. The temperature dependence of the real and imaginary part of the complex dielectric susceptibility in the vicinity of ferroelectric-paraelectric phase transition has been studied in the frequency region 100Hz-10mHz. The measurement of the dielectric constants of the real and imaginary parts shows strong frequency dependence. The investigations of the dielectric constant using Cole-Cole plots revealed a non-Debye-type dielectric relaxation for Ce+3 -doped SBN61. It reveals the coexistence of the two dielectric relaxators in the vicinity of the phase transition. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: cole-cole plots; dielectric relaxation; ferroelectrics